How French culture influences the framing of genetic modifications on the internet: Insights from Google-based corpus analysis. - Anaïs Degache; Séverine Louvel; Stéphanie Abrial; Virginie Tournay (PLoS ONE)
Since the mid-1990s, genetically modified (GM) crops and foodstuffs have been the subject of much controversy. While research has highlighted a disparity between attitudes toward the consumption of GM products, this study focuses on the circulation of cultural frameworks for GMs online. We use two datasets obtained using Google as a privileged observation site for understanding how debates regarding genetic engineering are framed in global and local contexts. While the English-language corpus brings to the fore the framing of GM products in terms of economic value, the French-language corpus is characterized by the strong association of such products with matters relating to risk. This has consequences for public perceptions of biotechnologies. Stakeholders using communication media to convey GM issues could assist public understanding by taking these cultural differences into account.